A Pilonidal Cyst as a Rare Cause of a Recurrent Nasal Hump: a Case Report and Literature Review - Drozdowski, Piotr; Jaworski, Aleksander P.; Drozdowska, Aneta; Ryczek, Anna; Sławińska, Barbara (Dermatology Review/Przegląd Dermatologiczny, 2025)
A pilonidal cyst is a rare cause of a dorsal nasal hump. The literature review showed that all pilonidal cysts in this area were congenital or post-traumatic, and iatrogenic lesions had not been reported. We present the case of a 22-year-old woman who has undergone rhinoplasty with the external approach using piezoelectric techniques. Despite successful initial surgery, she experienced a recurrence of the hump, requiring revision surgery. Following the dissection of the nasal dorsum, an encapsulated structure was visualized and removed. Yellowish cheese-like contents started to ooze from the structure. Histological assessment of the lesion confirmed the presence of a pilonidal cyst. Revision surgery complications were not reported, and a long-lasting and satisfactory aesthetic effect was achieved. The patient remains under close supervision. Apart from the typical recurrence of the cartilaginous hump, a pilonidal cyst, dermoid cyst, and a teratoma should be considered in the differential diagnosis.